Genomewide Comprehensive Analysis Reveals Critical Cooperation Between Smad and c‐Fos in RANKL‐Induced Osteoclastogenesis. (16th April 2015) - Omata, Yasunori; Yasui, Tetsuro; Hirose, Jun; Izawa, Naohiro; Imai, Yuuki; Matsumoto, Takumi; Masuda, Hironari; Tokuyama, Naoto; Nakamura, Shinya; Tsutsumi, Shuichi; Yasuda, Hisataka; Okamoto, Kazuo; et al.
ABSTRACT: We have previously reported that transforming growth factor β (TGF‐β) plays an essential role in receptor activator of nuclear factor‐κB ligand (RANKL)‐induced osteoclastogenesis. However, the detailed underlying molecular mechanisms still remain unclear. Formaldehyde‐assisted isolation of regulatory elements (FAIRE) and chromatin immunoprecipitation (ChIP) followed by sequencing (FAIRE‐seq and ChIP‐seq) analyses indicated the cooperation of Smad2/3 with c‐Fos during osteoclastogenesis. Biochemical analysis and immunocytochemical analysis revealed that physical interaction between Smad2/3 and c‐Fos is required for their nuclear translocation. The gene expression of nuclear factor of activated T‐cells, cytoplasmic 1 ( Nfatc1 ), a key regulator of osteoclastogenesis, was regulated by RANKL and TGF‐β, and c‐Fos binding to open chromatin sites was suppressed by inhibition of TGF‐β signaling by SB431542. Conversely, Smad2/3 binding to Nfatc1 was impaired by c‐Fos deficiency. These results suggest that TGF‐β regulates RANKL‐induced osteoclastogenesis through reciprocal cooperation between Smad2/3 and c‐Fos. © 2014 American Society for Bone and Mineral Research.